PENGARUH TUNJANGAN KESEJAHTERAAN DAN KESEHATAN TERHADAP PRESTASI KERJA PADA PT. TIRTA INDAH ABADI MELA (TIAM) - Ridaramawati Simanullang; Rosmita Ambarita; Rahmadiah Hanum (CV. ALIM'SPUBLISHING, 2025)
Based on the description of the results of research on the effect of welfare and health benefits on work performance at PT. Tirta Indah Abadi Mela (TIAM), it can be concluded as follows: Based on multiple correlation coefficients there is a sufficient/moderate and positive relationship of 0.6 between Welfare and Health Benefits on Work Performance, based on the Determination coefficient obtained at 0.687%, this means that the model's ability to explain variations in work performance by welfare and health benefits is 68.7% at PT. Tirta Indah Abadi Mela (TIAM) Work will increase by the coefficient (0.776) if the Health variable on Work Performance will increase by the coefficient (0.641) plus one unit, and based on the t test conducted on the proposed hypothesis it is accepted (significant) where t count is greater than t table which is 5.240 > 2.04227 which means the influence of Welfare and Health Benefits on Work Performance at PT. Tirta Indah Abadi Mela (TIAM). very sufficient and significant in increasing performance.